abc of maths

Algebra Level 3

If a b + c + b a + c + c a + b = 0 \frac{a}{b+c} + \frac{b}{a+c} + \frac{c}{a+b} = 0 and a + b + c = 5 a+b+c = 5 , the value of 1 b + c + 1 a + c + 1 a + b \frac{1}{b+c} + \frac{1}{a+c} + \frac{1}{a+b} can be expressed in the form m n \frac{m}{n} , where m m and n n are coprime, positive integers. Find the value of m + n m+n .


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Add b + c b + c + c + a c + a + a + b a + b = 3 \displaystyle \frac{b+c}{b+c} + \frac{c+a}{c+a} + \frac{a+b}{a+b} = 3 to the both sides we get

a + b + c b + c + a + b + c c + a + a + b + c a + b = 3 \displaystyle \frac{a+b+c}{b+c} + \frac{a+b+c}{c+a} + \frac{a+b+c}{a+b} = 3

5 ( 1 b + c + 1 c + a + 1 a + b ) = 3 \displaystyle 5\left(\frac{1}{b+c} + \frac{1}{c+a} + \frac{1}{a+b}\right) = 3

( 1 b + c + 1 c + a + 1 a + b ) = 3 5 \displaystyle \left(\frac{1}{b+c} + \frac{1}{c+a} + \frac{1}{a+b}\right) = \boxed{\displaystyle \frac{3}{5}} ~~~

brilliant and awesome!!!!!

Adarsh Kumar - 6 years, 10 months ago

ok it is correct

Khlout Sambath - 6 years, 10 months ago

Exactly the same way

Kushagra Sahni - 6 years, 10 months ago

so brilliant! now i can figure it out!

Nurhamizah Rashid - 6 years, 10 months ago

Wow! How do you possibly Figure these out?? XD

Mehul Arora - 6 years, 7 months ago
Felipe Hofmann
Jul 29, 2014

This is my first solution, I hope you enjoy it!

Let's wiggle with a b + c \frac{a}{b+c} . First, because a = 5 ( b + c ) a=5-(b+c) ,

a b + c = 5 ( b + c ) b + c = 5 b + c 1 \frac{a}{b+c} = \frac{5-(b+c)}{b+c} = \frac{5}{b+c} - 1 .......(1)

Analogously,

b a + c = 5 a + c 1 \frac{b}{a+c} = \frac{5}{a+c} - 1 ........................(2)

c a + b = 5 a + b 1 \frac{c}{a+b} = \frac{5}{a+b} - 1 ........................(3)

Adding (1), (2) and (3), because the LHS equals zero, we get

0 = 5 ( 1 b + c + 1 a + c + 1 a + b ) 3 ( 1 b + c + 1 a + c + 1 a + b ) = 3 5 0 = 5(\frac{1}{b+c}+\frac{1}{a+c}+\frac{1}{a+b}) - 3 \rightarrow (\frac{1}{b+c}+\frac{1}{a+c}+\frac{1}{a+b}) = \frac{3}{5}

Then, 3 + 5 = 8 3+5 = \boxed{8} , the answer.

Could someone tell me how to make my calculus bigger?

Felipe Hofmann - 6 years, 10 months ago

exactly the same way!!!

Kartik Sharma - 6 years, 10 months ago
Vaibhav Borale
Jul 30, 2014

mine mine

Qi Huan Tan
Jul 29, 2014

( a + b + c ) ( 1 b + c + 1 a + c + 1 a + b ) = a b + c + b a + c + c a + b + 3 (a+b+c)(\frac{1}{b+c}+\frac{1}{a+c}+\frac{1}{a+b})=\frac{a}{b+c}+\frac{b}{a+c}+\frac{c}{a+b}+3

5 ( 1 b + c + 1 a + c + 1 a + b ) = 0 + 3 5(\frac{1}{b+c}+\frac{1}{a+c}+\frac{1}{a+b})=0+3

1 b + c + 1 a + c + 1 a + b = 3 5 \frac{1}{b+c}+\frac{1}{a+c}+\frac{1}{a+b}=\frac{3}{5}

Gokul T.R.
Aug 31, 2014

Add 3 on both sides and distribute the three uniformly to all terms. Then take a+b+c common and solve the problem.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...